Direct superior approach versus posterolateral approach in mid-term clinical outcomes of total hip arthroplasty: a prospective randomized controlled study - Zhanqi Wei; Yiming Xu; Wei Zhu; Xisheng Weng; Bin Feng (BMC Musculoskeletal Disorders, 2025)
Abstract Purpose The aim of this study is to compare mid-term clinical outcome of direct superior approach (DSA) and posterolateral approach (PLA) in THA. Method Seventy-eight patients who underwent THA from January 2021 to June 2021 were prospectively enrolled and randomly allocated into DSA group and PLA group. The surgical duration, incision length, total blood loss, ambulation time, visual analogue scale (VAS), patient satisfaction, Harris hip score (HHS), Western Ontario and McMaster Universities Osteoarthritis (WOMAC) score, postoperative leg length discrepancy (LLD), abduction angle, anteversion angle and complications were compared between the two groups. Results Thirty three patients were randomized to the PLA group and 32 patients allocated to the DSA group. The average follow-up period was 39.8 months in DSA group and 40.1 months in PLA group. Compared with PLA group, DSA group had longer surgical duration ([124.1 ± 11.2] min vs. [103.3 ± 20.7] min), less total blood loss ([482.4 ± 236.1] ml vs. [680.2 ± 299.4] ml), shorter incision ([8.7 ± 1.9] cm vs. [15.6 ± 1.7] cm), and earlier ambulation time ([15.8 ± 4.0] h vs. [20.5 ± 3.5] h), with statistically significant differences (P < 0.0001). Furthermore, the DSA group had significantly lower WOMAC Scores compared to the PLA group at 1-year postoperatively (P = 0.011), and had significantly lower WOMAC Function Scores and WOMAC Stiffness Scores both at 1-year postoperatively and at the last follow-up. The anteversion angle of the cup in the DSA Group was significantly smaller than the PLA Group at postoperative day (POD) 3 and the last follow-up (P = 0.006 and P = 0.010, respectively). However, there was no difference in postoperative patient satisfaction, complication, LLD or HHS between the two groups. Conclusion DSA demonstrated benefits in terms of reduced blood loss, improved pain scores, shorter incisions, and earlier ambulation. These advantages support the use of DSA for promoting early recovery and better mid-term functional outcomes. Trial registration The study protocol was registered on Chinese Clinical Trial Register (ChiCTR) with the register number ChiCTR2000041186 (registration date: 2020/12/21).